Pattern and outcome of children admitted for burns in Benin City, mid-western Nigeria - O. O. Oludiran; P. F. A. Umebese (Indian Journal of Plastic Surgery)
Children are a vulnerable to burns, an injury, which is often preventable. A study of the profile of cases of children admitted for burns will provide background information to suggest locally doable preventive strategies as well as supply basic information for future reference. We studied the records of 62 children aged 0-16 years, admitted for burns, at the University of Benin Teaching Hospital, Benin City, between January 2002 and December 2006. There were 34 male and 28 female children. Children under three years constituted 56.5%. Whereas the leading cause of burns in all the children was flame burns from kerosene explosions (52%), scalds were responsible for 68.6% of cases in those under three. The extent of burn injury ranged from 6 to 50% and most of them presented late. 64.6% were discharged within three weeks. Wound sepsis and post burn contractures were the most frequently encountered complications (19.4% and 9.7% respectively). There were two deaths (3.2%) related to sepsis. Particular attention to burn safety precautions in children (especially, in the >3 years age group), safer storage and dispensing of combustible chemicals particularly petroleum products is advocated. Fire safety awareness, correct first aid measures and early presentation in the hospital will reduce morbidity and mortality. Early physiotherapy and splinting strategies will reduce contractures. There is the need locally for the establishment of specialized burn centres both to treat these children and to stimulate interest in burn management.